Transformational Leadership Among School Principals And Its Impact On The Effectiveness Of Decision-Making From The Teachers' Point Of View (Journal of Namibian Studies : History Politics Culture, 2023)
The study aimed to identify the transformational leadership among school principals and its impact on the effectiveness of decision-making from the point of view of teachers. The descriptive, correlational approach was used. The study sample consisted of (584) male and female teachers in public schools in Abha City. The questionnaire was used as a tool for collecting data. The results of the study showed that the level of school principals’ application of the transformational leadership method in government schools in Abha City was at a moderate degree, and the level of effectiveness of decision-making was at a moderate degree in government schools in Abha City from the point of view of teachers. The results also showed a positive relationship between transformational leadership and decision-making effectiveness in government schools in Abha City from the point of view of teachers, and that there is an impact of transformational leadership on the effectiveness of decision-making in public schools in Abha City from the point of view of teachers.